Dynamic changes in neuronal autophagy and apoptosis in the ischemic penumbra following permanent ischemic stroke - Yi-hao Deng; Hong-yun He; Li-qiang Yang; Peng-yue Zhang (Neural Regeneration Research, 2016)
The temporal dynamics of neuronal autophagy and apoptosis in the ischemic penumbra following stroke remains unclear. Therefore, in this study, we investigated the dynamic changes in autophagy and apoptosis in the penumbra to provide insight into potential therapeutic targets for stroke. An adult Sprague-Dawley rat model of permanent ischemic stroke was prepared by middle cerebral artery occlusion. Neuronal autophagy and apoptosis in the penumbra post-ischemia were evaluated by western blot assay and immunofluorescence staining with antibodies against LC3-II and cleaved caspase-3, respectively. Levels of both LC3-II and cleaved caspase-3 in the penumbra gradually increased within 5 hours post-ischemia. Thereafter, levels of both proteins declined, especially LC3-II. The cerebral infarct volume increased slowly 1–4 hours after ischemia, but subsequently increased rapidly until 5 hours after ischemia. The severity of the neurological deficit was positively correlated with infarct volume. LC3-II and cleaved caspase-3 levels were high in the penumbra within 5 hours after ischemia, and after that, levels of these proteins decreased at different rates. LC3-II levels were reduced to a very low level, but cleaved casp-ase-3 levels remained high 72 hours after ischemia. These results indicate that there are temporal differences in the activation status of the autophagic and apoptotic pathways. This suggests that therapeutic targeting of these pathways should take into consideration their unique temporal dynamics.